Netflix dan Mahasiswa: Analisis Empiris Perceived Value, Brand Engagement, dan Niat Penggunaan Lanjutan - Regita Yuliana Siregar; Marwan Marwan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of perceived value on continuance usage intention with customer brand engagement as a mediating variable in the context of Netflix video-on-demand service usage among students of the Faculty of Economics and Business, Universitas Negeri Padang. A quantitative approach was employed using a survey method through the distribution of questionnaires via Google Form. A total of 90 respondents were included in the sample. Data analysis was conducted using SmartPLS 3. The results reveal that perceived value has a positive but not statistically significant direct effect on continuance usage intention. In contrast, perceived value has a positive and significant effect on customer brand engagement, which in turn significantly influences continuance usage intention. Furthermore, customer brand engagement mediates the relationship between perceived value and continuance usage intention. These findings indicate that consumer engagement with the brand plays a crucial role in strengthening the impact of perceived value on the intention to continue using the service. The practical implication of this study suggests that Netflix should focus on enhancing consumer perceived value through content and pricing strategies, while also fostering emotional, cognitive, and behavioral engagement to sustain user loyalty and service continuity, particularly among university students.